Bacillus anthracis Edema Toxin Activates Nuclear Glycogen Synthase Kinase 3β - Larabee, Jason L. (American Society for Microbiology (ASM), 2008)
Bacillus anthracis edema toxin (ET) generates high levels of cyclic AMP and impacts a complex network of signaling pathways in targeted cells. In the current study, we sought to identify kinase signaling pathways modulated by ET to better understand how this toxin alters cell physiology. Using a panel of small-molecule inhibitors of mammalian kinases, we found that inhibitors of glycogen synthase kinase 3 beta (GSK-3β) protected cells from ET-induced changes in the cell cycle. GSK-3β inhibitors prevented declines in cellular levels of cyclin D1 and c-Jun following treatment of macrophages with ET. Strikingly, cell fractionation experiments and confocal immunofluorescence microscopy revealed that ET activates a compartmentalized pool of GSK-3β residing in the nuclei, but not in the cytoplasm, of macrophages. To investigate the outcome of this event, we examined the cellular location and activation state of β-catenin, a critical substrate of GSK-3β, and found that the protein was inactivated within the nucleus following intoxication with ET. To determine if ET could overcome the effects of stimuli that inactivate GSK-3β, we examined the impact of the toxin on the Wnt signaling pathway. The results of these experiments revealed that by targeting GSK-3β residing in the nucleus, ET circumvents the upstream cytoplasmic inactivation of GSK-3β, which occurs following exposure to Wnt-3A. These findings suggest ET arrests the cell cycle by a mechanism involving activation of GSK-3β residing in the nucleus, and by using this novel mechanism of intoxication, ET avoids cellular systems that would otherwise reverse the effects of the toxin.